Peran Perusahaan Avani Eco Dalam Menangani Krisis Sampah Plastik - Mochammad Basyiruddin Al Hazmi (Solidaritas, 2022)
A major global waste crisis is caused by petroleum-derived plastics, because they are difficult to decipher. Biodegradable plastics are plastics in which some or all of the raw materials are replaced with natural polymers. This study analyzes the role of the Avani Eco company in dealing with the plastic waste crisis in Bali. Companies engaged in the production of environmentally friendly plastics or biodegradable plastics note that the plastic waste crisis in Bali is quite alarming, so Avani wants to take part in dealing with the crisis. The method used is a qualitative method, where to get the data, the authors use related respondents to get concrete data. The results of the descriptive analysis so far, Avani Eco has succeeded in helping reduce the use of single-use plastic (PSP) both in Indonesia and abroad. In addition to production and sales activities, the AvaniEco company also carries out a marine conservation campaign assisted by several other non-profit organizations and the local government, so that the amount of plastic waste in the Bali sea begins to decrease quite a lot. According to the Bali Regional Government, 513 tons of plastic waste that enters Bali's waters and only about 12% can be recycled, so Avani Eco wants to contribute to reducing the amount of plastic waste in Bali. The success of marketing with the business to business concept has been very optimal, as many as 80% of Avani Eco's superior products penetrate the international market with a fairly large number of exports, so it is hoped that the awareness of the whole community can protect the environment with the presence of biodegradable plastic. Keywords: Plastic, Bali, Avani Eco, Crisis, Biodegradable